Relationship between anthropometric parameters and bonde density in 7-8-year-old rhythmic gymnasts - Parm, A.; Saar, M.; Pärna, K.; Jürimäe, K.; Neissaar, I.; Jürimäe, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Better bone density in childhood might prevent osteoporosis in later life (Baxter-Jones et.al., 2008). Prepubertal years are an opportune time to increase bone mineral density (BMD) through exercise (Bass et.al., 1998). High-impact exercise has strong impact to BMD and bone mineral content (BMC). Rhythmic gymnasts perform a lot of jumps and is known as high-impact bone loading sport. The aim of the study was to investigate the influence of anthropometric (skinfolds, girths, lengths and breadths) and body composition (fat %, fat mass, lean body mass - LBM) parameters to the BMD and BMC in young rhythmic gymnasts and same age controls. Methods: Participants of this study were 89 7-9 year-old girls from different schools and sport clubs. They were devided to the rhythmic gymnasts (n=46) and controls (n=43). Body height and body mass were measured and BMI was calculated (kg/m²). All anthropometric parameters were measured according to the protocol recommended by the International Society for Advancement of Kinanthropometry. BMI (g/cm³) and BMC (g) were determined by DXA. BMD and BMC were measured at lumbar spine (L2-L4) and femoral neck area. Results: Gymnasts have significantly higher values in L2-L4 and femoral neck BMD compared to controls. Gymnasts have also higher BMC values in L2-L4 and femoral neck compared to controls. Gymnasts had significantly lower values in skinfolds. Anthropometric values and bone parameters have significantly more relationships in controls compared to gymnasts. Discussion: Our results suggest that young rhythmic gymnasts body height, LBM and BMI are the same as in controls. However, in controls body fat mass and fat % are significantly higher and BMD and BMC in L2-L4 and femoral neck have lower values than gymnasts. From the anthropometric parameters skinfold thicknesses are thicker in controls, on the girths, lengths and breadths there are very few significant differences between rhythmic gymnasts and controls.